The Leading Practice of Decision Making in Modern Business Systems : Innovative Technologies and Perspectives of Optimization. - Popkova, Elena G. (Emerald Publishing Limited, 2019)
Concentrating on the Russian model, this book reflects the leading practical experience of decision making in modern business systems and presents innovative technologies and perspectives to optimize this process.